Studi Komposisi Bakteri dan Mikroalga pada Sistem Akuakultur Air Tawar - Meyta Pratiwi; Atang; Aulidya Nurul Habibah; Rizal Khoirun Alfisah (Biotropic : The Journal of Tropical Biology, 2026)
Freshwater aquaculture is still in demand by fish farmers to meet consumer demand for animal protein needs. Fish farming uses an intensive system to produce adequate amounts of fish, but it is followed by metabolite waste problems that can affect the quality of life of fish. Handling fish metabolite waste can be started by conducting a study of microbes that play a role in the decomposition of fish metabolite waste. The method used to determine the microbes is the survey method, by isolating culturable bacteria using nutrient agar (NA) and Winogradsky media, identifying microalga found in fish farming ponds, measuring the physico-chemical parameters of aquaculture pond water. The results obtained were five heterotrophic bacteria (106 cfu/mL), five nitrifying bacteria (105 cfu/mL), four phylum microalgae, and physico-chemical conditions of water (temperature 27 °C, TDS 76-78 mg/L, nitrates 2-2.7 mg/L, and pH 6.5-6.7). The microbes obtained are widely known to help the process of decomposing metabolite waste in fish farming ponds, so that they can be used as promised probiotic agents for aquaculture organisms in the future.